TRANSFORMASI PERDAGANGAN INTERNASIONAL MELALUI E-COMMERCE AMAZON: PERSPEKTIF PELAKU BISNIS KREATIF SURABAYA - Bagus Rachmadhani Firmansyah; Moch.Reza Ivaldianto; Hanum Salsabila; Risky Agustin Widyanti; Alexandra Deniriando siga; Arga Christian Sitohang (Widya Balina, 2025)
Advancements in digital technology have brought about major transformations in international trade, particularly with the rise of global e-commerce as the main method for distributing and promoting goods across nations. Amazon, being one of the biggest e-commerce platforms globally, exemplifies this shift by linking producers with consumers through technology and integrated logistics networks. For innovative entrepreneurs in Surabaya, recognized as a hub for the creative economy in the country, this environment provides chances to broaden their market reach but also requires them to adjust to the worldwide digital trading landscape. This research intends to explore how creative entrepreneurs in Surabaya view and approach the use of Amazon for international trading. It will concentrate on identifying shifts in marketing techniques, strategies for market entry, and challenges faced when participating in the global digital trading environment. The findings of this investigation are anticipated to enhance theoretical understanding in the field of digital economies and offer actionable insights to bolster the competitiveness of local creative entrepreneurs in adapting to the evolving global e-commerce market.